2018
DOI: 10.26858/est.v4i1.4974
|View full text |Cite
|
Sign up to set email alerts
|

Lecturer’s Attitude towards Advance Technology and Its Impact to the Learning Process: Case study in Tangerang City Campuses

Abstract: This research aimed to determine the qualifications of lecturers in the field of social science depended on the use of advance technology, especially the power points, the Internet, and social media site. The problem that some of the lecturers preferred to use the traditional way of teaching, such as whiteboard and marker, lectures. This study research was to observe the categories of lecturers' knowledge, ages and gender in using technology in the classroom. Also we sought lecturers' difficulty in using techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…They still possess a level of competence that is more technical and communicative than pedagogical, as the educational potential of ICT is not exploited for its effective incorporation in teaching-learning processes (teaching and evaluation) as well as in relation to research. This is corroborated by previous research which has found that university teaching staff have tended to develop their digital pedagogical competence in different ways [9][10][11][12]46].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…They still possess a level of competence that is more technical and communicative than pedagogical, as the educational potential of ICT is not exploited for its effective incorporation in teaching-learning processes (teaching and evaluation) as well as in relation to research. This is corroborated by previous research which has found that university teaching staff have tended to develop their digital pedagogical competence in different ways [9][10][11][12]46].…”
Section: Discussionsupporting
confidence: 86%
“…All these factors imply that teaching staff in general, and university teaching staff more specifically, must have a high level of digital training. Nonetheless, various studies confirm that university teaching staff continue to integrate ICT into their teaching practice in different ways as a result of vast differences in their levels of pedagogical ICT competence [9][10][11][12]. It is necessary, therefore, for professors to be committed to the educational purpose of providing their students with learning opportunities through innovative methodologies strategies where ICT is present in an active way [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the impact of engaging and empowering learning on the lecturer is acceptable. Technology would engage, empower lecturers to a new level of learning which is emerging technology tools and services to help lecturers develop the skills that they need for teaching in the 21st-century learning process (Mardiana, 2018). It is believed that by bringing the Internet into every classroom, would bring the world and a majority of relevant precious resources for learning, and not only the promise of increasing efficiencies and productivity but also it could be a catalyst for defining a new Jurnal Pendidikan Indonesia (JPI) | 157 approach to teaching and learning as a new knowledge-based (Tomorrow, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Some lecturers use the virtual learning environment only to provide notes and submit assignments, including a comprehensive reading list of books and articles for students to read. Surprisingly, the students do not read books; in fact, they pull them apart for quotes at assignment (Graham, 2016;Sweden, 2017;Mardiana, 2018).…”
Section: Introductionmentioning
confidence: 99%